A broadly conserved g-protein-coupled receptor kinase phosphorylation mechanism controls Drosophila smoothened activity. - Maier, D.; Cheng, S.; Faubert, D.; Hipfner, D.R. (PLoS Genetics, 2014)
Hedgehog (Hh) signaling is essential for normal growth, patterning, and homeostasis of many tissues in diverse organisms, and is misregulated in a variety of diseases including cancer. Cytoplasmic Hedgehog signaling is activated by multisite phosphorylation of the seven-pass transmembrane protein Smoothened (Smo) in its cytoplasmic C-terminus. Aside from a short membrane-proximal stretch, the sequence of the C-terminus is highly divergent in different phyla, and the evidence suggests that the precise mechanism of Smo activation and transduction of the signal to downstream effectors also differs. To clarify the conserved role of G-protein-coupled receptor kinases (GRKs) in Smo regulation, we mapped four clusters of phosphorylation sites in the membrane-proximal C-terminus of Drosophila Smo that are phosphorylated by Gprk2, one of the two fly GRKs. Phosphorylation at these sites enhances Smo dimerization and increases but is not essential for Smo activity. Three of these clusters overlap with regulatory phosphorylation sites in mouse Smo and are highly conserved throughout the bilaterian lineages, suggesting that they serve a common function. Consistent with this, we find that a C-terminally truncated form of Drosophila Smo consisting of just the highly conserved core, including Gprk2 regulatory sites, can recruit the downstream effector Costal-2 and activate target gene expression, in a Gprk2-dependent manner. These results indicate that GRK phosphorylation in the membrane proximal C-terminus is an evolutionarily ancient mechanism of Smo regulation, and point to a higher degree of similarity in the regulation and signaling mechanisms of bilaterian Smo proteins than has previously been recognized.